2019
DOI: 10.1186/s13064-019-0126-0
|View full text |Cite
|
Sign up to set email alerts
|

Degeneration of saccular hair cells caused by MITF gene mutation

Abstract: BackgroundWaardenburg syndrome (WS) is the consequence of an inherited autosomal dominant mutation which causes the early degeneration of intermediate cells of cochlear stria vascularis (SV) and profound hearing loss. Patients with WS may also experience primary vestibular symptoms. Most of the current WS studies did not discuss the relationship between WS and abnormal vestibular function. Our study found that a spontaneous mutant pig showed profound hearing loss and depigmentation. MITF-M, a common gene mutat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…During neural circuit formation, axons are thought to navigate series of intermediate targets or choice points until they reach their final destination ( Comer et al, 2019 ; Raper and Mason, 2010 ). This concept emerged from seminal studies of limb bud innervation in insects ( Bate, 1976 ; Bentley and Keshishian, 1982 ; Ho and Goodman, 1982 ; Palka et al, 1992 ) and has been generalized to all contexts of long-distance axon projections.…”
Section: Introductionmentioning
confidence: 99%
“…During neural circuit formation, axons are thought to navigate series of intermediate targets or choice points until they reach their final destination ( Comer et al, 2019 ; Raper and Mason, 2010 ). This concept emerged from seminal studies of limb bud innervation in insects ( Bate, 1976 ; Bentley and Keshishian, 1982 ; Ho and Goodman, 1982 ; Palka et al, 1992 ) and has been generalized to all contexts of long-distance axon projections.…”
Section: Introductionmentioning
confidence: 99%
“…They also proposed that MITF-M mutant pigs could provide an important animal model for cochlear implantation and cell therapy of patients with congenital hereditary deafness. In vestibular research, Du et al. (2019) studied characteristics and function of vestibular hair cells in miniature pigs with MITF-M mutation.…”
Section: Resultsmentioning
confidence: 99%
“…Previous investigations found that MC1R c.280_285del6 was more frequently presented in black rabbits, c.304_333del30 was recessive red/yellow, and c.[124A;125_130del6] was connected with Japanese brindling coat color [ 6 , 7 , 30 ]. The MITF gene polymorphism is known to be associated with the black and white colors in mice [ 31 ], pigs [ 32 ], cattle [ 33 ], horses [ 34 ], chickens [ 35 ], ducks [ 36 ], llamas [ 37 ], and so on. In this study, three SNPs (g.232587A < G, g.232650C < G, g.232766A < T) were found in the TB, SG, and SW breeds, and polymorphism distribution of the g.232587A < G sites were significantly different between TBs and SGs ( p < 0.01).…”
Section: Discussionmentioning
confidence: 99%